ACADEMIC LYCEUM STUDENTS OF THE MINISTRY OF INTERIOR AS ONE OF THE IMPORTANT CHARACTERISTICS OF PROFESSIONAL-PERSONAL PREPARATION - Ismailov Alisher Ulugbekovich (Galaxy International Interdisciplinary Research Journal, 2023)
During the years of independence, "a comprehensive legal system was created in the republic to protect the rights and freedoms and legal interests of citizens, maintain public order, ensure the safety of individuals, society and the state, and prevent and prevent crimes." plays an important role.